Recovery of savory compounds from mussel cooking side stream as circular economy solution - Monica Gutierrez; David San Martin; Jone Ibarruri; Giuseppe Foti; Carlos Bald; Nerea Goienetxea; Jaime Zufia; Bruno Iñarra (Environmental Challenges, 2024)
This work aims to demonstrate that it is possible to reduce the pollution of a food wastewater by promoting the recovery of valuable compounds as secondary raw material for other processes enhancing the company sustainability.For this purpose, the technical feasibility of the recovery of biomolecules present in the mussel cooking side streams had been tested, through concentration and stabilization technologies to obtain ingredients for savoury use. Among all the technologies for concentration of proteins from processing currents that are available on the market or those in an advanced stage of research, three have been selected following the technical and economic feasibility criteria: Vacuum evaporation (VC), nanofiltration (NF) and diafiltration (DF) with nanofiltration membranes. The values of protein recovery were higher than 70% in all the concentrated fractions. The maximum of protein concentration was 92% for VC. In the case of membrane concentration, the protein content in the concentrate was lower, around 75 and 80% for NF and DF respectively. In all cases, the retention of interesting biomolecules was efficient therefore, the salt content was the selection criteria for choosing the most suitable concentration process. Consequently, the final selected process was NF concentration followed by DF as it allowed to concentrate the main savoury compounds, such as glutamic acid, up to two-folds, while achieving highest reduction on salt content (from 2.4% to 1.4%), in food grade conditions within the legal microbiological criteria. Moreover, the final reduction in the organic matter load of the selected effluents was 91%, allowing the factory to comply with the discharge standards.